Placental Vitamin D Metabolism as Well as its Relations to Circulating Vitamin D Metabolites in Pregnancies - Nabila Sher Mohammad, Nighat Yasmeen, Zahhara Qazi, Kalsoom Tariq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Uncertainty exists about the impact of placental vit D metabolism on mother's blood levels of vit D in people. Objective: Awareness of placental vit D metabolism and how it affects the amount of vit D metabolites in mother's blood was one of the goals of this investigation. Methods: To take part in a 14-week controlled feeding experiment, 27 third-trimester singleton pregnant women in good health from Hayatabad Medical Complex during Jan 2022 to April 2022. Female trophoblasts in vitro were further treated using Vitamin D3-13C to investigate the synthesis of vit D intermediates. Results: In maternal tissue, there was a substantial connection between 24,25-Dihydroxycholecalciferol and 25-hydroxyvitamin D. These placental metabolites were also closely connected to the corresponding compounds found in maternal circulation. 3-epi-25-Hydroxyvitamin D3 and low density lipoprotein-related protein 2 with 25-hydroxyvitamin D; CYP2R1 with 3-epi-25-Hydroxyvitamin D3; Cubilin (CUBN) with 25-hydroxyvitamin D; CYP27B1 with 3-epi-25-Hydroxyvitamin D3 and 1,25-dihydroxyvitamin D and CYP24A1 with 25-hydroxyvitamin D, 24,25-Dihydroxycholecalciferol all showed positive relationships. Conclusion: Strong relationships between the levels of circulating vit D metabolites in pregnancy and a number of placental markers of vit D metabolism suggest the hypothesis that the profile of vit D metabolites in mother's blood is altered by the placenta. Keywords: 24,25-Dihydroxycholecalciferol (24,25(OH)2D3), 25-hydroxyvitamin D (25(OH)D3), 3-epi-25-Hydroxyvitamin D3 (epi-25(OH)D3), CYP2R1, CYP24A1